Pengaruh Pembangunan Bendungan Paselloreng Terhadap Pemenuhan Kebutuhan Air Irigasi pada Daerah Irigasi Gilireng - Ricky Zefri; Falci Isrami (Jurnal Teknik Sipil, 2023)
The construction of dams has an impact on increasing the availability of water in a certain area. The development of Sidrap Regency and Wajo Regency from year to year has caused the need of water for their residents  also increase. The construction of the Paselloreng Multipurpose Dam is expected to meet the water needs, especially during the dry season where the shortage is occurred and the planting intensity is 112%. In connection with the fulfillment of water needs from the constructed reservoir, it is necessary to analyze the water balance so the capability of Paselloreng Dam to fulfill the water needs could be evaluated.. According to the results of the research analysis, it was found that Paselloreng Reservoir can meet irrigation water needs using the rice-paddy-palawija cropping pattern starting early in November-2 to meet the maximum irrigation water requirement of 12.42 m3/s and the minimum requirement of 0.79 m3/s . The simulation results of the operation of the reservoir with the benefits of raw water and irrigation covering an area of ​​8,510 ha with a planting intensity of 270% for reliability above 80%. The simulation results have not taken into account the additional inflow discharge in the catchment area between the reservoir location and the Gilireng Weir location (water availability downstream of the reservoir). After the existence of a reservoir, the fulfillment of water needs can be fulfilled where before the existence of a reservoir.